Approaching non-violent extremists in the context of the war against terrorism - Cristina de Esperanza Picardo (2018)
The rise of home-grown Islamist terrorism over the last decade has become a pressing concern in Europe's counter-terrorism (CT) agenda. This particularly vexing aspect of the jihadist threat has compelled governments to adopt a more comprehensive policy architecture. This dissertation focuses on one particularly controversial aspect that governments are facing nowadays: the rise of not-violent extremist organizations. The research explores the three possible policy options towards not-violent extremist organizations: ban, toleration and cooperation. Their adequate study will require a comprehensive study not only about their relation to violent extremism, but about how their management by policy-makers can entail repercussions for extremist violence. The main hypothesis that this paper presents and defends is that the best policy option towards not-violent extremism is toleration. Though this strategy is not panacea, it maximizes the potential benefits of the existence of not-violent extremist organizations while minimizing possible backfires.